THE INFLUENCE OF LEADERSHIP STYLE, COMMUNICATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN THE BENTENG MICRO INDONESIA SHARIA COOPERATIVE AREA 10 IN LEBAK REGENCY AND BOGOR REGENCY - Indah Lestari; Ahmad Ripai; Muhi Mukti (Universitas La Tansa Mashiro, 2024)
This research aims to determine the impact of the influence of leadership style, communication and work environment on the performance of employees of the Benteng Micro Indonesia Sharia Cooperative Area 10 in Lebak Residence and Bogor Residence. This research describes in detail the role and function of leadership style, communication and work environment, analyzes the factors that have an influence on employee performance, and determines the indicators used to measure employee performance. The research method used is quantitative research, with a sampling technique carried out by collecting data from a number of employees through questionnaires. Data processing was carried out using the Statistical Package for the Social Sciences (SPSS) version 20. Simultaneous test results showed that leadership style had insignificant results on employee performance, while communication and work environment had significant results and had a positive effect on employee performance. These findings provide useful insights for cooperative area managers and all branch leaders, because they can take concrete steps to improve the performance of their employees.